2021
DOI: 10.1111/imm.13364
|View full text |Cite
|
Sign up to set email alerts
|

Interdependencies between Toll‐like receptors in Leishmania infection

Abstract: Multiple pathogen‐associated molecular patterns (PAMPs) on a pathogen's surface imply their simultaneous recognition by the host cell membrane‐located multiple PAMP‐specific Toll‐like receptors (TLRs). The TLRs on endosomes recognize internalized pathogen‐derived nucleic acids and trigger anti‐pathogen immune responses aimed at eliminating the intracellular pathogen. Whether the TLRs influence each other's expression and effector responses—termed TLR interdependency—remains unknown. Herein, we first probed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…S6 ), indicating that LPG acts on mitochondria through receptor-mediated signaling pathways. Several TLRs have been implicated in the recognition of Leishmania and Leishmania -derived components by various immune cell types and in the modulation of host cell responses to infection ( 35 39 ). We therefore sought to assess the contribution of TLRs to the induction of mitochondriogenesis triggered by L. donovani metacyclic promastigotes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6 ), indicating that LPG acts on mitochondria through receptor-mediated signaling pathways. Several TLRs have been implicated in the recognition of Leishmania and Leishmania -derived components by various immune cell types and in the modulation of host cell responses to infection ( 35 39 ). We therefore sought to assess the contribution of TLRs to the induction of mitochondriogenesis triggered by L. donovani metacyclic promastigotes.…”
Section: Resultsmentioning
confidence: 99%
“…Using BMM from Unc93b1 Letr/Letr mice ( 54 ), we found that in addition to TLR4, induction of mitochondrial biogenesis and of type I IFN expression by L. donovani metacyclic promastigotes requires endosomal TLRs. Several studies have highlighted the contribution of these receptors in the host response to various Leishmania species ( 37 39 , 41 , 48 52 , 78 ). Recent work revealed that TLR3 is the endosomal TLR that mediates type I IFN expression in response to L. donovani ( 53 ), consistent with the defective type I IFN expression in L. donovani -infected Unc93b1 Letr/Letr BMM.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are pattern recognition receptors of enter-mucosa inherent immunity recognizing pathogen-associated molecular patterns (PAMPs) ( 36 , 37 ), mainly monitoring the microbe balance in the enteric cavity, and transferring information to mucosa lamina propria cells ( 38 ). The normal intestinal epithelial cells (IECs) express rare TLR2 and TLR4, but TLR4 expression in UC patients is upregulated ( 39 ).…”
Section: Discussionmentioning
confidence: 99%